Effects of two modes of static stretching on muscle strength and stiffness - Herda, T. J.; Costa, P. B.; Walter, A. A.; Ryan, E. D.; Hoge, K. M.; Kerksick, C. M.; Stout, J. R.; Cramer, J. T. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The purpose of the present study was to examine the effects of constant-angle (CA) and constant-torque (CT) stretching of the leg flexors on peak torque (PT), EMGRMS at PT, passive range of motion (PROM), passive torque (PASTQ), and musculotendinous stiffness (MTS).